Association of Specific Leg Muscle Strength and Motor Features in Parkinson’s Disease - Chatkaew Pongmala; Chernkhuan Stonsaovapak; Austin Luker; Alexis Griggs; Miriam van Emde Boas; Jacob M. Haus; Nicolaas I. Bohnen (Parkinson's Disease)
Background. Postural instability and gait difficulties (PIGD) are a significant cause of falls, mobility loss, and lower quality of life in Parkinson’s disease (PD). The connection between PD progression and diminished strength in the lower limbs has been acknowledged. However, the identification of specific muscle groups linked to PIGD and non-PIGD motor features is still unknown. Objective. To explore the relationship between the strength of specific lower limb muscle groups, along with muscle mass, and their associations with PIGD, PIGD subtypes, and non-PIGD motor features in PD. Methods. 95 PD participants underwent detailed motor and non-motor test batteries, including lower limb isometric strength testing and whole-body lean mass assessments. Correlation analysis and univariate and multivariate linear/logistic forward stepwise regression were performed to test associations between PIGD and non-PIGD motor features with normalized value (z-score) of lower limb muscle strength and measures of lean mass. Results. Multivariate regression analysis, adjusted for age, gender, and levodopa equivalent dose, revealed that hip abductor strength was significantly associated with overall PIGD motor severity ratings (p<0.001), impaired balance (p<0.001), and non-PIGD Parkinsonian motor features (p<0.001). Conversely, hip extensor strength was significantly associated with falls, slow walking, and FoG motor features (p=0.016; p=0.003; p=0.020, respectively). Conclusion. We found that lower hip abductor strength was associated with PIGD and non-PIGD motor features. The association between non-PIGD motor features may suggest specific vulnerability of the hip abductors as part of a proposed brain-muscle loop hypothesis in PD. Moreover, lower hip extensor strength correlated with falls, slow walking, and FoG.